Donor-Derived CD123-Targeted CAR T Cell Serves as a RIC Regimen for Haploidentical Transplantation in a Patient With FUS-ERG+ AML - Yao, Sun; Jianlin, Chen; Yarong, Liu; Botao, Li; Qinghan, Wang; Hongliang, Fang; Lu, Zhang; Hongmei, Ning; Pin, Wang; Hu, Chen; Liangding, Hu; Bin, Zhang (Frontiers in Oncology, 2019)
Background: Allogeneic hematopoietic stem cell transplantation (allo-HSCT) following chemotherapy is part of standard treatment protocol for patients with acute myeloid leukemia (AML). FUS-ERG+ AML is rare but has an extremely poor prognosis even with allo-HSCT in remission, possibly due to its a leukemia stem cell (LSC)-driven disease resulting in chemotherapy resistance and a novel therapy is urgently required. It has been reported that FUS-ERG-positive AML expresses CD123, a marker of LSC, in some cases. CD123-targeted CAR T cell (CART123) is promising immunotherapy, but how to improve the complete remission (CR) rate and rescue potential hematopoietic toxicity still need to explore. Case Presentation: We used donor-derived CART123 as part of conditioning regimen for haploidentical HSCT (haplo-HSCT) in a patient with FUS-ERG+ AML who relapsed after allogeneic transplantation within 3 months, resists to multi-agent chemotherapy and donor lymphocyte infusion (DLI) and remained non-remission, aiming to reduce these chemotherapy-resistant blasts and rescue potential hematopoietic toxicity. The blasts in BM were reduced within two weeks and coincided with CAR copies expansion after CART123 infusion. The patient achieved full donor chimerism, CR with incomplete blood count recovery, myeloid implantation. Conclusion: Our results hints that CART123 reduce the chemotherapy-resistant AML blasts for FUS-ERG+ AML without affecting the full donor chimerism and myeloid implantation.